Rancang Bangun Aplikasi Pemetaan dan Perawatan Rambu Lalu Lintas Pada KTL Surabaya Berbasis WEB ( Studi kasus : Dinas Perhubungan – Pemkot Surabaya ) - Yanuar, Ferry; Sutanto, Teguh; Taufik, Vicky M (Jurnal JSIKA, 2012)
Department of Transportation Surabaya as government agencies engaged in public transport infrastructure where one job is to perform maintenance of traffic signs. Department of Transportation has set the traffic rules, which serve as the priority areas of infrastructure that is always monitored and rider behavior. Traffic signs are essential elements as information for road users in particular are driver of the motor vehicles. But in data collection and maintenance of the signs are so many rely on the Department of Transportation map and user manual files are marked. While the survey carried signs that can not run optimally. Sign repair history is not well documented, making pegawasan not go well. In addition the Department of Transportation already has a data GPS (Global Positioning System) location of signs, but only documented. Based on the above problems, we need an application that can handle the problems experienced by the Department of Transportation. The application in which consists of digital maps, survey schedule, handling and repair history. Digital maps are used to display the location of signs, schedule a survey for the survey beacon scheduling, handling repairs to display signs that have been surveyed and showing signs that have changed history. The results of the application that was created to assist the Department of Transportation in addressing the digital signs pointing the location, survey schedule for regular maintenance occurs, the results of the survey is expected to more quickly and may show signs of history. Keyword: Road sign, Transportation Department, google map v3